Genes Critical for Developing Periodontitis: Lessons from Mouse Models - de Vries, Teun J.; Andreotta, Stefano; Loos, Bruno G.; Nicu, Elena A. (Frontiers in Immunology, 2017)
Periodontitis is a destructive bacterial-induced inflammatory disease of the tooth-supporting tissues, the periodontium, caused by an aberrant immune response to the dental microbiome. The chronic inflammatory state of the periodontium activates bone resorbing osteoclasts, ultimately leading to degradation of alveolar bone surrounding the teeth. Since the etiology of periodontitis in humans is not fully understood, genetic mouse models may pinpoint indispensable genes for optimal immunological protection of the periodontium against tissue destruction. Until recently, mouse models were barely used to study periodontal disease, since mice are relatively resistant against bacteria-induced periodontitis. In the past decade, however, various mouse models with susceptibility to periodontitis have been identified, either with or without oral introduction of periodontitis-associated bacteria. This review describes the current knowledge of genes that are involved for a proper maintenance of a healthy periodontium in mice. Null mutations of genes required for leukocyte cell-cell recognition and extravasation (e.g. Icam-1, P-selectin, Beta2- integrin/Cd18), for pathogen recognition and killing (e.g. Tlr2, Tlr4, Lamp-2), immune modulatory molecules (e.g. Cxcr2, Ccr4, IL-10, Opg, IL1RA, Tnf-α receptor, IL-17 receptor, Socs3, Foxo1), and proteolytic enzymes (e.g. Mmp8, Plasmin) cause periodontitis, most likely due to an inefficient clearance of bacteria and bacterial products. Several mechanisms resulting in periodontitis can be recognized: 1) inefficient bacterial control by the polymorphonuclear neutrophils (defective migration, killing), 2) inadequate antigen presentation by dendritic cells or 3) exaggerated production of pro-inflammatory cytokines. In all these cases the local immune reaction is skewed towards a Th1/Th17 (and insufficient activation of the Th2/Treg) with subsequent osteoclast activation. Finally, genotypes are described that protect the mice from periodontitis: the SCID mouse, and mice lacking Tlr2 /Tlr4, the Ccr1/Ccr5, the Tnf-α receptor p55 and Cathepsin K by attenuating the inflammatory reaction and the osteoclastogenic response.